Phenotypic characteristics of B cells in Behcet's disease: Increased activity in B cell subsets - (:unkn) unknown (J RHEUMATOL PUBL CO, 1999)
Objective. Increased numbers of spontaneous Ig secreting B cells and elevated immunoglobulin levels have been described in Behcet's disease (BD), in addition to changes in numbers and activities of T cells, natural killer cells, and monocyte-macrophages. We investigated other characteristics of B cells in BD. Methods. B lymphocyte subsets (CD19+CD5+, CD19+CD13+, CD19+CD28+, CD19+CD33+, CD19+CD80+, CD5+CD19+CD45RA+, CD5+CD19+CD45RO+) were phenotypically evaluated in 50 patients with ED, 80 healthy subjects, and 20 other patients with rheumatoid arthritis (RA), systemic lupus erythematosus (SLE); and sepsis. Results. Although the B cell number (CD19+) was normal, CD13 and CD33 positive B cells were more numerous in ED and sepsis compared to healthy controls and patients with RA and SLE. The percentage of CD45RO positive B cells was higher in both ED and sepsis, while the percentage of CD80 positive B cells was high only in ED. There was no increase in the CD5+CD19+ B cell subset, previously shown to be increased in several autoimmune diseases. Naive (CD45RA) and memory (CD45RO) status of CD5+CD19+ and CD5-CD19+ B cells showed that CD45RA expression was higher in CD5+CD19+ B cells, whereas expression of both CD45RA and CD45RO was higher in the CD5-CD19+ B cell group compared with healthy controls. Conclusion. Although the total B cell number was normal, increased levels of activated and memory B cell subsets suggest a modified B cell function in BI, which may be related to a weak stimulus by an unknown external antigen.
Keywords: Behcet's disease; CD5+B lymphocytes; CD45RO; CD45RA; B-1 CELLS; SUPEROXIDE GENERATION; T-CELLS; ANTIGEN; BLOOD; EXPRESSION; LEUKEMIA; CD5; DIFFERENTIATION; INVOLVEMENT